Effect of Artificial Oocyte Activation on Intra-Cytoplasmic Sperm Injection Outcomes in Patients with Lower Percentage of Sperm Containing Phospholipase Cζ: A Randomized Clinical Trial - Nazarian, Hamid; Azad, Nahid; Nazari, Leila; Piryaei, Abbas; Heidari, Mohammad Hassan; Masteri Farahani, Reza; Karimi, Maryam; Ghaffari Novin, Marefat (Journal of Reproduction & Infertility, 2019)
Background: Artificial oocyte activation (AOA) is a specialized method in assisted reproductive technique (ART). According to increasing concern about using AOA, it is necessary to evaluate sperm-borne oocyte activating factors (SOAFs) including phospholipase C zeta (PLCζ). In this study, PLCζ before AOA was evaluated first and then the impact of AOA on pre-implantation embryo development was investigated. Methods: This prospective clinical trial enrolled couples subjected to ICSI. By evaluating PLCζ, semen samples were categorized into two groups; I (Control) and II (PLCζ deficient). Retrieved oocytes from partners were put into three categories: control group (Injected with sperm from group I, n=113), group without AOA (Injected with sperm from group II and no exposure to AOA, n=106), and group AOA (Injected with sperm from group II and exposure to AOA, n=114). Finally, fertilization results were compared via Kruskal-Wallis followed by Dunn’s multiple comparison test. The p<0.05 was considered statistically significant. Results: Fertilization rate was significantly lower in the group without AOA compared to control group (41.9±6.3 vs. 78.1±4.7, p<0.001). AOA improved fertilization rate in group AOA compared to the group without AOA (69.5±3.9 vs. 41.9±6.3, p<0.01); however, cleavage (91.7±2.8, 90.9±4.6, and 95.2±3.4, respectively) and embryo quality (2.5±0.1, 2.3±0.2, and 2.4±0.2, respectively) scores were not substantially different between groups of control, with and without AOA. Conclusion: We showed that PLCζ can be considered as a good biomarker in evaluation of oocyte activation capability. Further studies are required to establish the best use of PLCζ as a biomarker in clinics.